Radial microwire array solar cell with pyramidal structure. (October 2016) - Priyadarshini, Bindu; Das, Mukul Kumar; Sen, Mrinal; Kumar, Subindu
Abstract: In this work, a theoretical model for radial p-n junction microwire array solar cell with pyramidal structures in the space between microwires has been developed. Incorporation of pyramidal structures results in reflection of light, which would otherwise be unused, and illuminates side walls of the microwires. This additional illumination enhances absorption and, hence, efficiency of the whole structure. Efficiency enhancement is analyzed by varying different device parameters e.g., radius and length of each microwire and packing fraction of the structure. Results show that the maximum fractional efficiency enhancement can be obtained as 30% by suitable choice of these parameters. Highlights: Efficiency enhancement is observed in Microwire solar cell by incorporating pyramidal reflectors in between the Microwires. Theoretical model has been developed to calculate efficiency. Results show that improved efficiency can be obtained while reducing the material cost.